UMSU STUDENTS' PREFERENCE IN USING QRIS AS A DIGITAL PAYMENT TECHNOLOGY - Ramadhan, Rizky; Wahyudi, Andre; Frisca, Syifa; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study is to determine the interest of University of Muhammadiyah North Sumatra (UMSU) students in using QRIS as a digital payment method in Indonesia. The approach used in this study uses a qualitative approach. The respondents in this study were students of the Sharia Business Management study program, Faculty of Islamic Religion, UMSU. This article explores qualitative approaches through interview methods in the context of research. Based on this research in order  to improve the efficiency and security of digital payment transactions and also to facilitate transactions for students. Special emphasis is given to the excellence of interviews as a data collection tool that allows researchers to establish direct interaction with UMSU students of the Islamic business management study program. By discussing the advantages and challenges of using QRIS. The results of this study show that performance expectations and facilitating conditions have an influence on students' interest in using QRIS as a payment technology.